Pengaruh Green Accounting, Material Flow Cost Accounting, dan Ukuran Perusahaan terhadap Kinerja Perusahaan dengan Nilai Perusahaan sebagai Variabel Moderating (Studi pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di BEI Tahun 2 - Muhammad Abdul Aris; Shafira Selena Orlin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the effect of green accounting, material flow cost accounting, and company size on company performance which is moderated by company value. The type of research used is secondary data quantitative research with a population of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2019-2022. The total sample amounted to 86 using purposive sampling method from financial report data or annual reports available on the Indonesia Stock Exchange or on the relevant company website. The data analysis method used is multiple regression analysis and moderated regression analysis (MRA). Company performance is proxied by return on assets (ROA). The results showed that green accounting, material flow cost accounting (MFCA), and company size had an effect on company performance. On the other hand, the fourth, fifth, and sixth hypotheses of firm value were unable to moderate the influence between green accounting, material flow cost accounting (MFCA), and company size on company performance.